Narratology, hermeneutics, and Midrash: Jewish, Christian, and Muslim narratives from the late antiquity through to modern times - Cordoni, Constanza; Langer, Gerhard (Poetik, Exegese und Narrative, 2014)
The contributions compiled in this volume comprise studies of Jewish texts - biblical, rabbinic, medieval, and modern -, as well as of patristic and medieval Christian texts, and in one case, a passage of the Muslim text par excellence, the Quran. The authors, scholars in the fields of Jewish Studies, Catholic and Protestant Theology, Islamic Studies, German philology etc., invited to reflect on texts of their respective disciplines in context-sensitive interpretations, taking into account the link connecting Midrash, hermeneutics, and narrative, provide illuminating narratological and/or hermeneutical insights into the texts in question. The interdisciplinary dialogue that characterized the conference 'Narratology, Hermeneutics, and Midrash' that gave rise to the volume proves to be rich and full of potential for further research in the direction proposed by the Series Poetics, Exegesis and Narrative. Studies in Jewish literature and art. Constanza Cordoni is assistant researcher at the Institute for Jewish Studies at the University of Vienna since 2009. Dr Gerhard Langer is professor at the Institute for Jewish Studies at the University of Vienna.